2021
DOI: 10.1111/cts.13176
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association analysis of warfarin dose requirements in Middle Eastern and North African populations

Abstract: To date, there has been no genomewide association study (GWAS) from the Middle East and North African (MENA) region to identify genetic variants associated with warfarin dose variability using this approach. In this study, we aimed to conduct the first GWAS of warfarin dose requirements in patients from the MENA region. A total of 132 Qatari (discovery) and 50 Egyptians (replication) were genotyped using Illumina Multi‐Ethnic Global BeadChip Array. A GWAS was performed on log‐transformed weekly warfarin dose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The genetic variants within VKORC1 rs9934438 and CYP2C9 rs4086116 explained 39 and 27% of the variability in the weekly warfarin dose requirement in the Qatari and Egyptians, respectively. These results are consistent with previous studies that have shown that VKORC1 and CYP2C9 are the main genetic factors influencing warfarin dose response ( 34 ).…”
Section: Pgx Researchsupporting
confidence: 93%
“…The genetic variants within VKORC1 rs9934438 and CYP2C9 rs4086116 explained 39 and 27% of the variability in the weekly warfarin dose requirement in the Qatari and Egyptians, respectively. These results are consistent with previous studies that have shown that VKORC1 and CYP2C9 are the main genetic factors influencing warfarin dose response ( 34 ).…”
Section: Pgx Researchsupporting
confidence: 93%
“…Genome-wide association studies have confirmed that the most important warfarin pharmacogenomic variants are found in two genes, CYP2C9 and VKORC1 ( Cooper et al, 2008 ; Takeuchi et al, 2009 ; Cha et al, 2010 ; Perera et al, 2013 ; Parra et al, 2015 ; El Rouby et al, 2021 ). It is also known that the most important variants will differ between populations, which has been mainly attributed to differences in minor allele frequencies (MAFs) of these variants ( Cavallari and Perera, 2012 ; Johnson et al, 2017 ).…”
Section: Genetic Variants Influencing Warfarin Responsementioning
confidence: 99%
“…Whereas pharmacogenomic algorithms that incorporate both genetic and non-genetic factors can account for about half of the variability in warfarin daily dose requirements in Whites ( Table 1 ), they explain only about a third in Blacks, meaning that Blacks and other underrepresented populations could benefit from more studies to identify additional genetic variants. Although the majority of previous association studies used a candidate-gene approach, genome-wide association studies (GWASs) ( Cooper et al, 2008 ; Takeuchi et al, 2009 ; Cha et al, 2010 ; Perera et al, 2013 ; Parra et al, 2015 ; El Rouby et al, 2021 ) which systematically search the entire genome for new genetic factors have also been undertaken. One study in particular ( Perera et al, 2013 ) was able to identify a new genetic variant ( CYP2C rs12777823) that significantly altered dose requirements independent of the effects of CYP2C9*2 , CYP2C9*3 , and VKORC1 -1639G > A .…”
Section: Future Directions In Warfarin Pharmacogenomic Researchmentioning
confidence: 99%
“…The effect of genetics on bleeding events in patients treated with this drug was also assessed. Four genetic variants increasing the expression of EPHA7 gene were found in the African American population, where the incidence of bleeding in patients treated with warfarin is higher [ 134 ].…”
Section: Stroke Pharmacogenomicsmentioning
confidence: 99%